Pengaruh Kepemimpinan Transformasional, Kompetensi dan Motivasi Kerja terhadap Kinerja Penyuluh Pertanian di Badan Penyuluhan dan Pengembangan SDM Pertanian Kementerian Pertanian - Dony Supriyanto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The performance of agricultural extension workers plays a strategic role in improving farmers’ capacity and agricultural productivity, yet it is influenced by multiple organizational and individual factors. This study aims to examine the effect of transformational leadership, competence, and work motivation on the performance of agricultural extension workers at the Agency for Agricultural Extension and Human Resource Development, Ministry of Agriculture. A quantitative explanatory approach was employed using multiple linear regression analysis. Data were collected through questionnaires distributed to 62 respondents selected using simple random sampling. The analysis included t-tests, F-tests, and the coefficient of determination to evaluate both partial and simultaneous effects. The findings indicate that competence and work motivation have a positive and significant effect on performance, while transformational leadership shows a positive but statistically insignificant effect. Simultaneously, all independent variables significantly influence performance, with a coefficient of determination (R²) of 71.9%, indicating that the model explains a substantial proportion of performance variation. These results highlight the importance of strengthening employee competence and motivation to improve organizational outcomes in agricultural extension services.